Individually Perceived Stress as a Mediator Between High Accomplishment Work Practices and Firm Performance - Khan, Areeba; Siddiqui, Sulaman Hafeez; Saeed, Sohail; Habib, Asmara (Review of economics and development studies (Online), 2020)
This research paper investigates the mediatory effect of Individually Perceived Stress in the direct relationship of high accomplishment work practices and financial performance of Firm. This research narrates different mechanisms and procedure through which work practices enhances firm performance. Cross Sectional research design is opted for data collection purpose. Data is collected from 500 employees of banking industry and analysis of data is done through Confirmatory Factor Analysis and Multiple Regression Analysis. The analysis of collected data shows that Individually Perceived Stress significantly affects the direct relationship of High-Performance Work Practices and Firm Financial Performance. Stress changes the direction of implemented practices in opposite direction due to which resultant results doesn’t match with the desired results. This paper contributes to literature by responding to the long waiting call for explaining importance of stress in high performance work practices and firm performance linkage. This paper also strengthens the literature by adding individual effect of four constructs of   High Performance Work Practices. Current research also holds important and valuable implications for governing bodies or managing authorities of institutions.